International Radio Spectrum Management Regime: Restricting or Enabling Opportunistic Access in the TVWS? - Mohamed El-Moghazi; Jason Whalley; James Irvine (International Telecommunications Society (ITS), 2016)
The practice of TV white spaces (TVWS), one application of the easement approach to spectrum management, has varied around the world with limited commercial deployments and only a few trials due mainly to the delay in digital switchover and the resistance of broadcasters. Internationally the ITU-R has discussed, at the World Radiocommunication Conference of 2012 (WRC-12), the regulatory measures that can enable deployment of cognitive radio systems (CRS). Following WRC-12, the ITU-R has started to discuss TVWS among other dynamic spectrum access (DSA) techniques. The examination of the influence of the international spectrum regime on national spectrum policy reform, from command and control towards spectrum easements approach is based on data collected from 84 interviews and shows that the international regime does not prevent adopting opportunistic access in the TVWS. However, there are different elements of flexibility (support) and restriction (opposition) that have an influence on a regulator's decision regarding the deployment of such a concept. These elements are dependent on a country's relationship with its neighbours, the perception of the TVWS concept and the interpretation of the ITU-R Radio Regulations (RR). There are four different perceptions on the TVWS radiocommunication service status: secondary, non-interference basis, primary, and different status according to the perceived operation of TVWS. There are contrasting perceptions on the influence of WRC-12 decision on CRS regarding TVWS adoption. There are two distinct views on the need for particular measures similar to those adopted for WLAN in the 5 GHz for TVWS such as dynamic frequency selection (DFS). This is based on the perception of TVWS service status, deficiencies of TVWS, deficiencies of DFS, difference between operation of WLAN and TVWS and positive influence of such measures on the TVWS adoption. Finally, it is argued that the TVWS proponents were quite unlucky in terms of the timing of its deployment due to the consecutive mobile allocations in the 800 MHz, 700 MHz, 470-694 MHz spectrum bands by the WRC-07, WRC-12, and WRC-15 respectively. These have significantly reduced TVWS chances in the whole UHF band.
Keywords: 330